Pharmacotherapy and treatment options for HIV-associated nephropathy. (2nd January 2018) - Menez, Steven; Hanouneh, Mohamad; McMahon, Blaithin A.; Fine, Derek M.; Atta, Mohamed G.
ABSTRACT: Introduction : Human immunodeficiency virus (HIV) remains a worldwide disease with significant mortality and morbidity. There are a multitude of HIV-related kidney diseases including HIV-associated nephropathy (HIVAN) most prominently. The risk of developing HIVAN increases with decreasing CD4 count, higher viral load, and based on genetic factors. The mortality rate for those with HIVAN-end stage renal disease (ESRD) remains 2.5–3 times higher than ESRD patients without HIVAN. Areas covered : The epidemiology of HIVAN, particularly risk assessment, will be explored in this review. Further, the pathogenesis of HIVAN, from viral-specific renal expression to the role of genetics as well as characteristic renal pathology will be described. Diagnosis and management of HIVAN will be addressed, with an emphasis on various treatment strategies including medication, dialysis, and kidney transplantation. Expert opinion : HIVAN is associated with a high risk for progression to ESRD and increased mortality. The backbone of HIVAN therapy remains combined anti-retroviral therapy (cART), while adjunctive therapies including RAAS blockade and prednisone, should be considered. In those who progress to ESRD, dialysis remains the mainstay of management, though increasing evidence has demonstrated that kidney transplantation can be effective in those with controlled HIV disease.